PENGARUH TENURE AUDIT, ROTASI AUDIT, AUDIT FEE TERHADAP KUALITAS AUDIT DENGAN KOMITE AUDIT SEBAGAI VARIABEL MODERASI (Studi Pada Perusahaan Sektor Keuangan yang Terdaftar di BEI Tahun 2010 2014) - Ardani, Sarifah Vesselina (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2017)
This study is an attempt to analyze the influence of Tenure Audit, Audit Rotation,Audit Fee to the Audit Quality with Audit Committee as a moderating variable. Thepopulation of this study are 81 financial sector companies listed in BEI 2010-2014,and the sample is 33 companies. The type of data used in this study is secondarydata obtained from the website of the Indonesia Stock Exchange is www.idx.co.idand added with various information from the website of each company. Theempirical result of the study exhibit that Tenure Audit and Audit Fee variable have aneffect to Audit Quality, while Audit Rotation variable has no effect to Audit Quality.The Audit Committee is unable to moderate all independent variables.